2016
DOI: 10.7448/ias.19.1.21140
|View full text |Cite
|
Sign up to set email alerts
|

High levels of pre‐treatment HIV drug resistance and treatment failure in Nigerian children

Abstract: IntroductionPre-treatment HIV drug resistance (PDR) is an increasing problem in sub-Saharan Africa. Children are an especially vulnerable population to develop PDR given that paediatric second-line treatment options are limited. Although monitoring of PDR is important, data on the paediatric prevalence in sub-Saharan Africa and its consequences for treatment outcomes are scarce. We designed a prospective paediatric cohort study to document the prevalence of PDR and its effect on subsequent treatment failure in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
25
2
Order By: Relevance
“…Additionally, we compared the profile of the DRMs in two Pretreatment drug resistance in cell-free RNA occurring above 20% frequency is known to be a strong predictor of early virological failure in children. 48,49 In this study, the signature DRM associated with ART were not observed in cell-free RNA at baseline. Although University database, we found that a few DRM associated with specific ART regimen were found at a higher frequency in drugexposed subjects infected with HIV-1C and a few other DRM identified through the present study were not found.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Additionally, we compared the profile of the DRMs in two Pretreatment drug resistance in cell-free RNA occurring above 20% frequency is known to be a strong predictor of early virological failure in children. 48,49 In this study, the signature DRM associated with ART were not observed in cell-free RNA at baseline. Although University database, we found that a few DRM associated with specific ART regimen were found at a higher frequency in drugexposed subjects infected with HIV-1C and a few other DRM identified through the present study were not found.…”
Section: Discussioncontrasting
confidence: 50%
“…Pretreatment drug resistance in cell‐free RNA occurring above 20% frequency is known to be a strong predictor of early virological failure in children . In this study, the signature DRM associated with ART were not observed in cell‐free RNA at baseline.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…There is however comparatively little available data from less developed countries where non-B subtypes predominate. In Nigeria where the epidemic is largely driven by non-B subtypes, reports on HIV drug resistance and polymorphisms [12][13][14][15][16][17][18][19][20][21] have primarily focused on resistance to non-nucleoside reverse transcriptase inhibitors (NNRTIs) and nucleoside reverse transcriptase inhibitors (NRTIs) while resistance to Protease inhibitors (PI) remain understudied. Since the commencement of ART program in Nigeria in 2001, government has collaborated with some donor agencies such as Global Fund to Fight AIDS, Tuberculosis, and Malaria and US President's Emergency Plan for AIDS Relief (PEPFAR) to scale up its ART clinics.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of PDR on the response to a first-line regimen has been difficult to quantify as resistance testing prior to initiating ART is used to guide therapy in high-resource regions. However, there have been at least 13 studies in which a first-line NNRTI-based ART regimen was initiated either according to public health guidelines [5][6][7][8][9][10][11][12][13][14][15] or a clinical trial protocol [16,17] and for which stored samples were available to assess the impact of pretreatment DRMs on virological success. These studies included about 340 persons with PDR.…”
mentioning
confidence: 99%